Reverse total shoulder arthroplasty with allograft bone block augmentation following proximal humerus sarcoma resection: a novel technique and case report of two patients - Hammad, Ahmad M.; Merkabaoui, Haya M. El; Hammad, Mahmoud M.; Saghieh, Said S. (International Surgery Journal, 2024)
There are several options for endoprosthetic replacement of the proximal humerus following oncologic resections. Reverse total shoulder arthroplasty (RTSA) has gained popularity in recent years for reconstruction, and bone allograft can be used to restore bone stock and improve implant survival. Patient A (67 years female) and patient B (62 years female) with sarcoma of the proximal humerus underwent tumor resection with wide margins and reconstruction with cemented reverse total shoulder arthroplasty. The construct was augmented with allograft bone blocks to decrease burden of osteotomy length and bone defect and improve prosthesis coverage and stability. RTSA with bone block augmentation is functionally stable and effective following massive tumor resection. Controversy still exists on the ideal construction method and more research is needed for assessment of outcomes and appropriate patient selection.